A review and synthesis of correlates of fatigue in osteoarthritis. (May 2019) - Hackney, Alisha J.; Klinedinst, N. Jennifer; Resnick, Barbara; Renn, Cynthia; Fiskum, Gary
Abstract: Fatigue affects nearly half of all adults with osteoarthritis. Affected individuals report difficulty with daily functioning, requiring more time and rest during activities, feeling easily exhausted, and having to give up on social and volunteer activities known to improve quality of life. Because its etiology is poorly understood, clinical practice guidelines are unable to address management of fatigue in osteoarthritis. Elucidating a mechanism of osteoarthritis fatigue is a high priority, but few studies have identified key factors associated with fatigue in osteoarthritis. Thus, the purpose of this narrative literature review is to present the current evidence of known and potential correlates of fatigue in osteoarthritis, and synthesize our findings into a conceptual framework. The overarching goal of this work is to provide insight into areas of needed research and guide future work toward mechanistic insight of osteoarthritis fatigue. This knowledge could lead to novel nursing interventions for prevention, management, and treatment of fatigue among adults with osteoarthritis.